HUBUNGAN DUKUNGAN SUAMI TERHADAP PEMBERIAN ASI EKSKLUSIF 6-11 BULAN DIKELURAHAN KARUWISI UTARA KOTA MAKASSAR - mustamin mustamin; abdullah tamrin; Putri Anggraeny (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Backgrounds: Mother's Milk (ASI) is the only food that contains all the nutrients needed for baby growth 0-6 months. Based on the results of Riskesdas (2010), shows infants who received exclusive breastfeeding in Indonesia only 15.3%. Of 136.7 million babies born worldwide only 32.6% of those exclusively breastfed within the first 6 months. While based on data obtained from the Monitoring of Nutrition Status (PSG) of South Sulawesi Province in 2016, the percentage of children under five to age 6 got exclusive breastfeeding in Makassar City 27.5% and South Sulawesi 38.5%, but this achievement is still low when compared with A national target of 80% of infants receiving exclusive breastfeeding.Objectives: To identify the relationship of husband support to Exclusive Breastfeeding 6-11 months in North Karuwisi Urban of Makassar City.Methods: The design of this study is a cross-sectional survey study.